The Effect of Bamboo Dancing Learning Method on Interest, Motivation, and Learning Outcomes in Electricity Law - Widhi Dwi Nugroho; I. Irwanto; Bagus Dwi Cahyono (Universitas Pendidikan Indonesia, 2023)
This study aimed to determine the effect of bamboo dancing learning on the learning interest of industrial electronics engineering students and the effect of bamboo dancing learning methods on students' interest in studying electricity law. Students in tenth grade have demonstrated increased interest, motivation, and learning outcomes in industrial electronics engineering courses taught using the bamboo dancing method. The research utilized a quasi-experimental design, and the experimental method employed a control group design with non-equivalent participants. The findings demonstrated several points: (i) the bamboo dancing learning method does not affect interest, (ii) the bamboo dancing affects student motivation, and (iii) the bamboo dancing method affects the learning outcomes of the laws of electricity. The experimental class increased the learning outcomes of students who participated in learning the material of the law of electricity. The bamboo dancing method increased students' interest, motivation, and academic achievement.